The effects of derivative use on equity fund performance - Koskela, Elina (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Investing in mutual funds has become more popular than ever and the amount of money invested in mutual funds registered in Finland has hit its all-time high. Mutual funds provide a relatively low-cost method for private investors to invest in stock market and achieve diversified portfolios. In finance there is always a tradeoff between risk and return, where higher expected returns can usually be achieved only by taking higher risks. Diversifying the portfolio gets rid some of the risk but systematic risk cannot be diversified away. These risks can be managed by hedging the investments with derivatives. The use of derivatives should improve the performance of the portfolios using them compared to the funds that don’t. However, previous studies have shown that the risk exposure and return performance of derivative users does not considerably differ from nonusers. The purpose of this study is to examine how the use of derivatives affects the performance of equity funds. The funds studied were 155 equity funds registered in Finland in 2013. Empirical research was done by studying the derivative use of the funds during a 6-year period between 2008–2013. The performance of the funds was studied quantitatively by using several different performance measures used in mutual fund industry; Sharpe Ratio, Treynor Ratio, Jensen's alpha, Sortino Ratio, M2 and Omega Ratio. The effect of derivative use on funds' performance was studied by using a dummy variable and comparing performance measures of derivative-users and nonusers. The differences in performance measures between the two groups were analyzed with statistical tests. The hypothesis was that funds' derivative use should improve their performance relative to the funds that don't use them. The results of this study are in line with previous studies that state that the use of derivatives does not improve mutual funds' performance. When performance was measured with Jensen's alpha, funds that did not use derivatives performed better than the ones that used them. When measured with other performance measures, the results didn’t differ between two groups.

Rahastosijoittamisen suosio on kasvanut viime vuosina ja Suomeen rekisteröityihin rahastoihin on virrannut pääomaa enemmän kuin koskaan ennen. Sijoitusrahastot tarjoavatkin suhteellisen edullisen tavan piensijoittajille sijoittaa osakemarkkinoille ja päästä käsiksi hajautettuun portfolioon. Sijoittamisen luonteeseen kuuluu, että suurempien tuottojen mukana tulevat myös suuremmat riskit. Portfoliota hajauttamalla voidaan päästä eroon osasta riskiä, mutta systemaattista riskiä ei voida hajauttaa. Tältä riskiltä voidaan kuitenkin suojautua käyttämällä portfoliossa johdannaisia. Johdannaisten käytön tulisi parantaa portfolion suoriutumista verrattuna portfolioon joka ei niitä käytä. Tutkimukset ovat kuitenkin osoittaneet, että johdannaisia käyttävien portfolioiden riskiprofiili ja tuotot eivät juurikaan eroa johdannaisia käyttämättömistä. Tämän tutkimuksen tarkoituksena on tutkia miten johdannaisten käyttö vaikuttaa osakerahastojen suoriutumiseen riskikorjatuilla tuotoilla mitattuna. Tutkimusaineisto koostui 155 Suomeen vuonna 2013 rekisteröidystä osakerahastosta. Empiirinen tutkimus suoritettiin tutkimalla johdannaisten käyttöä rahastoissa vuosina 2008–2013. Rahastojen suoriutumista tutkittiin kvantitatiivisesti käyttämällä useita erilaisia riskikorjattua tuottoa mittaavia tunnuslukuja, joita käytetään rahastomarkkinoilla; Sharpe Ratiota, Treynor Ratiota, Jensenin alfaa, Sortino Ratiota, M2:a ja Omega Ratiota. Johdannaisten käytön vaikutusta tutkittiin dummy-muuttujan avulla vertaamalla tunnuslukuja johdannaisia käyttäneiden ja käyttämättömien välillä. Eroja tunnusluvuissa kahden ryhmän välillä analysoitiin tilastollisten testien avulla. Lähtökohtana oli, että johdannaisten käytön tulisi parantaa rahaston suoriutumista verrattuna johdannaisia käyttämättömiin. Tämän tutkimuksen tulokset ovat linjassa aiempien tutkimusten kanssa, joiden mukaan johdannaisten käyttö ei paranna rahastojen suoriutumista. Kun tunnuslukuna käytettiin Jensenin alfaa rahastot jotka eivät käyttäneet johdannaisia suoriutuivat paremmin kuin rahastot jotka käyttivät. Kun tunnuslukuna käytettiin muita tunnuslukuja, tulokset eivät eronneet ryhmien välillä